Analisis Determinan Ketimpangan Pembangunan Ekonomi Antar Wilayah di Kawasan Gerbangkertosusila - Ananta, Daffa Adli; Asmara, Kiky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the determinants of inter-regional economic inequality in the Gerbangkertosusila metropolitan area of East Java, Indonesia, covering seven districts and cities over the period 2016–2025. Economic inequality is measured using the Williamson Index, which recorded values ranging from 0.801 to 0.870 throughout the observation period, indicating persistently high inequality. The independent variables examined include gross regional domestic product (GRDP) per capita, population size, investment realization, open unemployment rate, and mean years of schooling. This study employs a quantitative approach using panel data regression, with model selection determined through the Chow Test and Hausman Test, both of which confirmed the Fixed Effect Model as the most appropriate estimator. Classical assumption tests for multicollinearity, heteroscedasticity, and autocorrelation were conducted and all assumptions were satisfied. The estimation results indicate that GRDP per capita, population, and mean years of schooling have a significant positive effect on economic inequality, while investment and the open unemployment rate are statistically insignificant. The positive effect of mean years of schooling suggests that unequal educational attainment across districts accelerates brain drain toward the urban core, thereby widening rather than reducing regional disparities. These findings are consistent with Kuznets's (1955) inverted-U hypothesis, Myrdal's (1957) cumulative causation theory, and the Harris–Todaro (1970) migration model. The study contributes empirical evidence to support more spatially equitable regional development policy in metropolitan areas.